Preface. Numerical Algebra, Control and Optimization - Wang, Song; Wu, Yong Hong (2012)
This Special Issue was intended to be dedicated to Charles Pearce, a Distinguished Professor at The University of Adelaide, on the occasion of his 70th birthday and in recognition of his many fundamental contributions in Applied Mathematics, Pure Mathematics and Mathematical Statistics. However, as this Special Issue is sent to print, we received the shocking news that Professor Charles Pearce was killed in a car accident near Fox Glacier, New Zealand on Friday, 9 June, 2012. With great sadness, we wish to dedicate this Special Issue to the late Charles Pearce in memory of his achievements in the elds and contributions to the mathematical communities.